Colonial families in motion : tracing the Nelson New Zealand Company Assisted Emigrants, 1810-1910 : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in History at Massey University, Auckland, New Zealand. EMBARGOED until 1 December 2026. - Garside, Susan Jane (Massey University, 2024)
The New Zealand Company’s assisted emigrants who arrived in the first stage of organized British colonization of Aotearoa play an emblematic role in many accounts of this country’s national history, as the founders of early colonial communities. While their arrival as part of a scheme inspired by Edward Gibbon Wakefield’s theories is well documented, how their lives later unfolded is much less clear. Existing historiography seldom challenges a widely held popular view of them as a relatively homogenous group of ‘labourers’ who became foundational ‘settlers’ in a New Zealand Company colony. This thesis contributes to a deeper understanding of nineteenth-century migration from Europe and the colonisation of Aotearoa New Zealand by examining the experiences of more than 3000 assisted emigrants who arrived in the Nelson New Zealand Company colony, from 1841-44. It identifies their origins, explores how they came to emigrate, and follows them to the end of their lives, tracing their movements from Nelson to other parts of New Zealand, and beyond. It explores patterns of migration and mobility and applies a range of considerations in assessing the emigrants' experiences, and their success or otherwise. As many of the New Zealand Company’s assisted emigrants were too poor to be visible in many historical sources, genealogy research methods, including the use of commercial genealogy databases and research tools, were incorporated into this research. Records from this ‘wild archive’ were pivotal in revealing the complexities of the Nelson emigrants' lives. In doing so, this research highlights how a substantial number were not in fact permanent 'settlers' in Nelson. The majority moved, sometimes within the province, sometime to places elsewhere in New Zealand, and one in five left New Zealand all together. Some did well in life, others not so well, and their social and financial position was often as fluid as their geographic location. Through the rich detail from the ‘wild archives,’ this research highlights how family networks and relationships were ultimately the most important influences across the emigrants’ vast range of outcomes.
Keywords: nineteenth-century migration, colonisation, New Zealand history, genealogy, mobility, family, Nelson, New Zealand company, assisted emigrants, English migrants, German migrants, British migrants, return migration, nineteenth-century land ownership; 430320 New Zealand history